2013
DOI: 10.1111/jam.12238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant secondary compounds on in vitro methane, ammonia production and ruminal protozoa population

Abstract: Aims: The objective of this study was to evaluate the potential of secondary plant metabolites from 38 sources to serve as antimethanogenic additives in ruminant diets. The effect of leaf tannins from these different plant sources on rumen fermentation, protozoal populations and methanogenesis was also studied. Methods and Results: Samples (200 mg dry matter, DM) were incubated without and with polyethylene glycol (PEG)-6000 (400 mg DM) as a tannin binder during 24-h incubation in the in vitro Hohenheim gas sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 27 publications
3
36
1
Order By: Relevance
“…In a study by Tan et al (2011), 33% reduction in in vitro CH 4 production at the inclusion of 10 mg of purified CT from Leucaena/500 mg DM had been observed. In a study by Bhatta et al (2013), it was shown that plant leaves containing secondary metabolites as their contents such as Rauvolfia serpentine, Indigofera tinctoria and Withania somnifera have great potential to suppress methanogenesis with minimal adverse effect on feedstuff fermentation. Zmora et al (2012) indicated that Mentha piperita (MP) leaves which contain different classes of secondary metabolites at a concentration of 16.34 and 23.35 mg of MP to the 233.30 mg of substrate decreased rumen methane production at 24 h of incubation by altering the rumen micro-organisms' profiles without changing the profile of VFA and DM digestibility.…”
Section: Microorganismmentioning
confidence: 99%
“…In a study by Tan et al (2011), 33% reduction in in vitro CH 4 production at the inclusion of 10 mg of purified CT from Leucaena/500 mg DM had been observed. In a study by Bhatta et al (2013), it was shown that plant leaves containing secondary metabolites as their contents such as Rauvolfia serpentine, Indigofera tinctoria and Withania somnifera have great potential to suppress methanogenesis with minimal adverse effect on feedstuff fermentation. Zmora et al (2012) indicated that Mentha piperita (MP) leaves which contain different classes of secondary metabolites at a concentration of 16.34 and 23.35 mg of MP to the 233.30 mg of substrate decreased rumen methane production at 24 h of incubation by altering the rumen micro-organisms' profiles without changing the profile of VFA and DM digestibility.…”
Section: Microorganismmentioning
confidence: 99%
“…CH 4 accounts for 2‐12% loss of dietary gross energy in ruminants and is a potent greenhouse gas with a global warming potential 23 times higher than that of carbon dioxide (CO 2 ) in trapping the heat (Bhatta et al . ; Intergovernmental Panel on Climate Change (IPCC) ). Therefore, reducing ruminal CH 4 not only improves the efficiency of nutrient utilization but also helps to protect the environment from global warming.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the high CP content of the plant (29.2% DM). High CP of Indigofera had been also reported by some authors and generally ranged from 23-27% DM (Kaitho et al, 1998;Tscherning et al, 2006;Bhatta et al, 2012;Bhatta et al, 2013). In vitro dry matter (IVDMD) and organic matter digestibility (IVOMD) values of the experimental concentrates were 65.5-71.5% and 63.0-68.1%, respectively, while the in vitro crude protein digestibility (IVCPD) values were 79.1-83.8% (Figure 1).…”
Section: Resultsmentioning
confidence: 90%